The Effectiveness and Impact of Salary Subsidy Program on Community Purchasing Power - Rachmaniar Myrianda Dwiputri; Eka Pariyanti; Eman Sulaiman; Vigory Gloriman Manalu (International Journal of Ecma Science, 2021)
The Covid-19 pandemic not only affected health, but also the economy and community purchasing power to decrease, this was due to the many reductions in salaries and job layoffs made by companies. To overcome this, the government created a salary subsidy assistance program, with the hope of increasing community purchasing power. This study aims to analyze the effectiveness and impact of the salary subsidy program on community purchasing power that using the inflation indicator. This study uses descriptive analysis to explain the effectiveness of the salary subsidy assistance program and its impact on community purchasing power. The results show that, so far, the salary subsidy program has been effective and can increase community purchasing power.